Ảnh hưởng của trải nghiệm giao hàng chặng cuối tới sự hài lòng và lòng trung thành của khách hàng Gen Z trong thương mại điện tử B2C: Vai trò điều tiết của hình ảnh thương hiệu - Phạm Kiên, Trung; Lê Văn, Chiến; Nguyễn Thị, Hường (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study assesses the relationship among last-mile delivery experience, customer satisfaction, and loyalty among Gen Z customers in B2C e-commerce, examining the moderating role of brand image. The research employs a quantitative approach by employing the PLS-SEM structural model. Analysis of a survey of 365 Gen Z individuals in Hanoi reveals that the last-mile delivery experience positively influences the satisfaction and loyalty of Gen Z in B2C e-commerce. While brand image enhances the relationship with satisfaction, its impact on the loyalty of Gen Z is not found. The authors offer discussions and make recommendations for business managers based on the findings.
Keywords: Brand image; Customer loyalty; Satisfaction of Gen Z; Last-mile delivery experience; B2C e-commerce